Transcriptomics reveals a distinct metabolic profile in T cells from severe allergic asthmatic patients - Pablo-Torres, Carmela; Garcia-Escribano, Carlota; Romeo, Martina; Gomez-Casado, Cristina; Arroyo Solera, Ricardo; Bueno-Cabrera, José Luis; del Mar Reaño Martos, M.; Iglesias-Cadarso, Alfredo; Tarín, Carlos; Agache, Ioana; Chivato, Tomás; Barber, Domingo; et al. (Frontiers in Allergy, 2023)
The reasons behind the onset and continuation of chronic inflammation in individuals with severe allergies are still not understood. Earlier findings indicated that there is a connection between severe allergic inflammation, systemic metabolic alterations and impairment of regulatory functions. Here, we aimed to identify transcriptomic alterations in T cells associated with the degree of severity in allergic asthmatic patients. T cells were isolated from severe (n = 7) and mild (n = 9) allergic asthmatic patients, and control (non-allergic, non-asthmatic healthy) subjects (n = 8) to perform RNA analysis by Affymetrix gene expression. Compromised biological pathways in the severe phenotype were identified using significant transcripts. T cells' transcriptome of severe allergic asthmatic patients was distinct from that of mild and control subjects. A higher count of differentially expressed genes (DEGs) was observed in the group of individuals with severe allergic asthma vs. control (4,924 genes) and vs. mild (4,232 genes) groups. Mild group also had 1,102 DEGs vs. controls. Pathway analysis revealed alterations in metabolism and immune response in the severe phenotype. Severe allergic asthmatic patients presented downregulation in genes related to oxidative phosphorylation, fatty acid oxidation and glycolysis together with increased expression of genes coding inflammatory cytokines (e.g. IL-19, IL-23A and IL-31). Moreover, the downregulation of genes involved in TGFβ pathway together with a decreased tendency on the percentage of T regulatory cell (CD4 + CD25+), suggest a compromised regulatory function in severe allergic asthmatic patients. This study demonstrates a transcriptional downregulation of metabolic and cell signalling pathways in T cells of severe allergic asthmatic patients associated with diminished regulatory T cell function. These findings support a link between energy metabolism of T cells and allergic asthmatic inflammation.